In vitro germination of Passiflora gibertii N. E. Brown with mechanical scarification and gibberellic acid - Carvalho, Milene Alves de Figueiredo; Paiva, Renato; Vargas, Daiane Peixoto; Porto, Jorge Marcelo Padovani; Herrera, Raírys Cravo; Stein, Vanessa Cristina (Semina: Ciências Agrárias, 2012)
The objective of this work was to study the in vitro germination of Passiflora gibertii N. E. Brown seeds, regarding the scarification type, the effect of using GA3 growth regulator and the use of fresh or dry seeds. Ripe fruit seeds were washed in water and dried for four days (dry seeds). After this period, new seeds were isolated from fruits and washed in water (fresh seeds). Different scarification methods were tested (removing the tip seed by using forceps and scalpel or with sandpaper and the control treatment with no scarification). After scarification, seeds were inoculated in MS culture medium, containing half of its salt concentration supplemented with different concentrations of GA3 (0, 28.87, 57.74, 86.61 and 115.47 ?M) and were kept in a growth room under controlled conditions. The experimental design used was completely randomized in a triple factorial scheme 3x2x5 (scarification type, fresh or dry seeds and GA3 concentration) with four replications per treatment, each one consisting of five test tubes and each tube containing one seed. The evaluation was carried out in intervals of two days for 45 days. The percentage of germinated seeds and the germination speed index (GSI) were observed. Highest averages for the variables analyzed were obtained with the seed tip scarification by using forceps and scalpel. The highest percentage of germination was obtained for dry seeds with the seed tip scarification. The GA3 growth regulator addition to the culture medium had no effect on the analyzed variables.